Challenges and Interventions in Arts and Crafts Education: A Qualitative Analysis of Grade IV Students - Manggato, Sandra Dwi Chikitha; Lagandesa, Yun Ratna; Nashrullah, Nashrullah; Hariana, Kadek; Wilade, Surahman (Journal of Innovation and Research in Primary Education, 2025)
The main issue addressed in this study is the learning difficulties in Visual Arts and Crafts (Seni Rupa dan Prakarya) experienced by fourth-grade students at SDN 1 Bunta, along with the efforts made by teachers to overcome these challenges. The study aims to identify the contributing factors to the learning difficulties encountered by students in the Visual Arts and Crafts subject, particularly focusing on a class of 22 students, two of whom were identified as having significant learning challenges. It also seeks to explore the strategies employed by teachers in supporting these students. Data were collected through observation, interviews, and documentation. The results show that the learning difficulties in Visual Arts and Crafts stem from both internal and external factors. Internal factors include physical and psychological conditions of the students. External factors involve influences from the family, school environment, and broader community. The efforts undertaken to address these difficulties include the use of appropriate learning models, providing additional lessons tailored to the subject matter, assigning homework, and offering remedial teaching.